2017
DOI: 10.1007/s10823-017-9321-9
|View full text |Cite
|
Sign up to set email alerts
|

Carer Characteristics and Health, Wellbeing and Employment Outcomes of Older Australian Baby Boomers

Abstract: Supporting caregivers and enabling continued workforce participation are central strategies in Australia's response to an ageing population, however these strategies have potential disadvantages for carers, particularly women, including reduced workforce participation and retirement income, and poorer health status. This paper explores the nexus between paid work and caregiving for Australia's baby boomer cohort as this group faces unprecedented pressures to manage paid work alongside caring longer and more in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 59 publications
2
29
0
Order By: Relevance
“…Much research on caring intensity has used binary thresholds to explore its impact on employment (Carmichael & Charles, ; Carr et al, ; King et al, ; O'Loughlin et al, ). Consistent with these studies, when applying different cut‐points we found that caring for as few as 10 or more hours per week, compared to less than 10 hr, was significantly associated with not being employed for both mental health and other condition carers.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Much research on caring intensity has used binary thresholds to explore its impact on employment (Carmichael & Charles, ; Carr et al, ; King et al, ; O'Loughlin et al, ). Consistent with these studies, when applying different cut‐points we found that caring for as few as 10 or more hours per week, compared to less than 10 hr, was significantly associated with not being employed for both mental health and other condition carers.…”
Section: Discussionmentioning
confidence: 99%
“…Intensive caring has been linked to lower employment rates among carers for people with any condition, where intensity is measured by the hours of support provided or related factors such as the care recipient's level of impairment or whether they receive paid assistance (Carmichael, Charles, & Hulme, ; Lilly et al, ; Pickard, Brimblecombe, King, & Knapp, ). In Australia, O’Loughlin, Loh, and Kendig () found that older adults caring for 10 or more hours per week had only half the full‐time employment rate of those caring for fewer than 10 hr. Similarly, Leigh () identified a significant reduction in employment rates among carers providing more than 10, or more than 35 weekly hours of support.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased caregiving hours and having a care recipient live with a carer have been found to negatively influence carers’ labour force participation (ABS, ). In a recent study of 1,261 Australian men and women aged 60–64 years, O'Loughlin, Loh and Kendig () found women carers were more likely to be working and more likely to be employed part‐time than non‐carers. In the current study, carers were more likely to be employed part‐time or not working at all, rather than to be employed full‐time.…”
Section: Discussionmentioning
confidence: 99%
“…The association between education and work participation at 65 years or over was stronger among women than men. Education strengthened women's attachment to the labour market, allowing them to improve financial security by working for longer and higher educational qualifications had a 'health protective' effect (O'Loughlin et al 2017a). However, proactive gendered education policies were not evident.…”
Section: Education and Trainingmentioning
confidence: 99%